PENGARUH KOMPENSASI, LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KEPUASAN KERJA KARYAWAN OUTSOURCING PT GARUDA GENERAL SERVICE - Farhan Habib Muhammad Zhen (2021)
This research is conducted with the aim of testing the effect of compensation, work environment and job stress on employee job satisfaction empirically. In this study using independent variables, compensation, work environment and work stress with job satisfaction as dependent variable. The type of this research using quantitive research. The sample used is outsourced employees of PT Garuda General Service using a saturation sampling. Respondent data obtained by questionnaires distributed directly to 32 employees. The data analysis technique used is the t test and the coeffiecient determination using the SmartPls 3.0 software and the f (simultaneous) test manually. The results of this study stated that a significant effect was found in the relationship between compensation and job satisfaction, a significant effect was found in the relationship between work environment and job satisfaction, no significant effect was found between job stress and job satisfaction, then compensation, work environment and job stress had an significant effect simultaneuosly on job satisfaction.